Assistance in Making Form Design and Recording Medical Records for Toddlers at Posyandu Kutilang, Sukowiyono Village, Kec. Padas, Ngawi Regency - Wahyu Wijaya Widiyanto; Sri Wulandari; Artika Fristi Firnawati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
In the activities of Posyandu Kutilang, Sukowiyono Village, Kec. Padas, Kabupaten Ngawi, a health check was carried out by a health center health worker, but there was no form of a toddler's medical record that could be used to document the results of a health examination. The target of this community service activity is the Posyandu Kutilang posyandu participants. Guidance and consultation was carried out by Lecturers and Students of the Department of Medical Records and Health Information at the Indonusa Polytechnic Surakarta when accompanying cadres of Posyandu Kutilang, Sukowiyono Village, Kec. Padas, Ngawi Regency in documenting the health history of toddler participants. The assistance provided includes how to fill out medical record forms for toddlers, what items must be filled in, and how to manage forms. Health checks are only recorded in the agenda book for elderly examinations belonging to the Mobile Puskesmas, so that the participants of Posyandu Kutilang, Sukowiyono Village, Kec. Padas, Kabupaten Ngawi cannot monitor the results of monthly health checks. Results of Assistance in Making Form Design and Recording Medical Records for Toddlers at Posyandu Kutilang, in the hall of Posyandu Kutilang, Sukowiyono Village, Kec. Padas, Ngawi Regency was attended by 11 people. Activities started according to the agreed schedule. The training participants participated in the activity enthusiastically because they felt that this activity had a role in administrative order through the implementation of recording in the form / resume of toddler medical records.